Impact of Constitutional Court Decision 70/2024 on Regional Head Elections - Ravina Nayla Putri; Ahmad Ahmad; Wilda Ayu Anggraeni; Pudjiyawati Pudjiyawati (Indonesian Journal of Law and Policy Studies, 2023)
The Constitutional Court Decision No. 70/PUU-XXII/2024 introduces a revised understanding of the timeline for meeting the minimum age criteria for candidates running for regional head positions. Specifically, this requirement must be satisfied at the moment the General Election Commission announces the candidate pairs, rather than at the time of their inauguration. This article seeks to examine the implications of this ruling on the conduct of regional head elections in Indonesia, considering both legal and political dimensions. From a legal standpoint, the decision necessitates modifications to existing regulations and technical policies, which the General Election Commission and relevant stakeholders must promptly implement. Politically, this ruling compels political parties and regional head candidates to refine their nomination and campaign strategies with greater caution. Utilizing a normative legal approach, this article illustrates that while the Constitutional Court decision enhances legal certainty in the electoral process, it also introduces new dynamics in local political practices that require equitable and constitutional management